Asikainen&Macêdo: borders between art and science (Palíndromo, 2020)
In this interview, journalist Néri Pedroso talks to Henna Asikainen and Silvana Macêdo about their retrospective show entitled Untranslatable (2018), which celebrates the 20 years of collaboration between the two artists. We address questions about the content and formal outcome of their collaborative research and artistic practice, their dialogues with science, their environmental and social concerns, aspects of their biographies, languages and landscapes from their contrasting countries of origin, Finland and Brazil. The interview with Henna Asikainen was translated into Portuguese, but we also included the original English version at the end of the text.
Keywords: artistic collaboration; contemporary art; art and science